Lived Religion and Everyday Life in Early Modern Hagiographic Material - Kuuliala, Jenni; Peake, Rose-Marie; Räisänen-Schröder, Päivi (Palgrave Studies in the History of Experience, 2019)
1. Introduction: Hagiography & Lived Religion; Jenni Kuuliala, Rose-Marie Peake, and Päivi Räisänen-Schröder -- 2. Intimate Enemies: Religious Difference in Seventeenth-Century French Catholic Hagiography; Barbara B. Diefendorf -- 3. Gentle Holiness in the Vocational Culture of Seventeenth-Century French Visitandine Nuns; Christopher J. Lane -- 4. Saintly Shepherdesses: Semi-religious Women and Identity Formation in Seventeenth-Century France; Rose-Marie Peake -- 5. From an Experiencer to a Saintly Man: Losing Biography, Gaining Hagiography in the Accounts of Marian Apparitions in Early Modern Poland; Tomasz Wiślicz -- 6. Sleeping with the Enemy: Infertility and Wife Murder in a Miracle of St. Peter Martyr; Diana Bullen Presciutti -- 7. ‘When the Fury of the Proud Sea Re-Awoke’: Water, Devotion, and Lived Experience in Renaissance Venice; Karen McCluskey -- 8. Everyday Miracles in Seventeenth-Century Spain; Thomas C. Devaney -- 9. Narrating Pain and Healing in Andrieu de la Vigne, Mystère de saint Martin (1496); Andreea Marculescu -- 10. The Seriousness of Comedy in the ‘Redentin Easter play’ (ca. 1460): Forms, Functions, and Potential Effects; Florian M. Schmid -- 11. Cure, Community, and the Miraculous in Early Modern Florence; Jenni Kuuliala -- 12. The Sacred in Everyday Spaces: Discerning African Voices in the Canonisation Inquest of San Pedro Claver; Ronald J. Morgan